Of knowledge and work - Ben Dankbaar; Geert Vissers (Max Planck Institute for the Study of Societies, 2009)
The idea of the knowledge economy has brought with it a new paradigm of work that espouses the professionalization of all work. This new paradigm is now affecting the organization of work throughout the economy. However, not all work is knowledge work, whatever definition is used. The number of 'professionals' may rise, but many workers still face rather traditional working conditions. Moreover, we argue, the expected growth in the share of knowledge work may be less than expected: along with the forces pushing for an increase in knowledge work, there are also forces counteracting these. We develop a simple typology of work that takes autonomy and frequency of external contacts as dimensions. Workplaces with high autonomy and frequent external contacts (with customers and other stakeholders) are considered 'paradigmatic' for knowledge work. Using data from the European Working Conditions Survey (EWCS), we analyze the distribution of the European workforce across different types of work. Analysis of EWCS data (1995, 2000, 2005) shows that 'paradigmatic' knowledge work is actually shrinking. We offer a first, tentative explanation of this remarkable trend. – – Die Idee der 'Wissensökonomie' beinhaltet ein neues Paradigma der Professionalisierung von Arbeit, das Einzug in die Organisation der Arbeit der gesamten Wirtschaft gehalten hat. Doch nicht jede Arbeit ist Wissensarbeit, wie auch immer man diese definiert. Die Anzahl der 'Wissensarbeiter' mag steigen, doch sehen sich viele Arbeitnehmer weiterhin durchaus traditionellen Arbeitsbedingungen gegenüber. Darüber hinaus, so die Argumentation der Autoren, kann das erwartete Wachstum des Anteils der Wissensarbeit noch geringer ausfallen als erwartet: Neben Trends, die einen Anstieg der Wissensarbeit fördern, gibt es auch solche, die dagegenhalten. Das Papier entwickelt eine einfache Typologie wissensbasierter Arbeit, in deren Zentrum die Autonomie der Arbeitnehmer und die Häufigkeit externer Kontakte stehen. Arbeitsplätze mit hoher Autonomie und häufigen externen Kontakten (mit Kunden und anderen Akteuren) werden als 'paradigmatisch' für Wissensarbeit gewertet. Die Verteilung der Arbeitskraft in Europa auf verschiedene Beschäftigungstypen wird anhand von Datenmaterial des European Working Conditions Survey (EWCS) aus 1995, 2000 und 2005 analysiert. Die Ergebnisse zeigen, dass 'paradigmatische' Wissensarbeit eher rückläufig ist. Das Papier versucht eine erste Erklärung dieser überraschenden Entwicklung.
Keywords: 300